The effects of ambient temperature and feeding regimens on cecum bacteria composition and circadian rhythm in growing rabbits - Shuai He,; Zhang, Ke-Hao; Jin, Qiong-Yu; Wang, Qiang-Jun; Huang, Jie; Li, Jun-Jiao; Guo, Yao; Liu, Peng; Liu, Zhong-Ying; Liu, Dan; Geng, Shi-Xia; Li, Qin; et al. (Frontiers in Microbiology, 2024)
Seasonal environmental shifts and improper eating habits are the important causes of diarrhea in children and growing animals. Whether adjusting feeding time at varying temperatures can modify cecal bacterial structure and improve diarrhea remains unknown. Three batches growing rabbits with two groups per batch were raised under different feeding regimens (fed at daytime versus nighttime) in spring, summer and winter separately, and contents were collected at six time points in one day and used 16S rRNA sequencing to investigate the effects of feeding regimens and season on the composition and circadian rhythms of cecum bacteria. Randomized forest regression screened 12 genera that were significantly associated with seasonal ambient temperature changes. Nighttime feeding reduced the abundance of the conditionally pathogenic bacteria Desulfovibrio and Alistipes in summer and Campylobacter in winter. And also increases the circadian rhythmic Amplicon Sequence Variants in the cecum, enhancing the rhythm of bacterial metabolic activity. This rhythmic metabolic profile of cecum bacteria may be conducive to the digestion and absorption of nutrients in the host cecum. In addition, this study has identified 9 genera that were affected by the combination of seasons and feeding time. In general, we found that seasons and feeding time and their combinations affect cecum composition and circadian rhythms, and that daytime feeding during summer and winter disrupts the balance of cecum bacteria of growing rabbits, which may adversely affect cecum health and induce diarrhea risk.